2023
DOI: 10.34133/research.0124
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 RBD and Its Variants Can Induce Platelet Activation and Clearance: Implications for Antibody Therapy and Vaccinations against COVID-19

Abstract: The COVID-19 pandemic caused by SARS-CoV-2 virus is an ongoing global health burden. Severe cases of COVID-19 and the rare cases of COVID-19 vaccine-induced-thrombotic-thrombocytopenia (VITT) are both associated with thrombosis and thrombocytopenia; however, the underlying mechanisms remain inadequately understood. Both infection and vaccination utilize the spike protein receptor-binding domain (RBD) of SARS-CoV-2. We found that intravenous injection of recombinant RBD caused significant platelet clearance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Since we found that spike protein could upregulate platelet integrin αⅡbβ3 outside‐in signaling, such as platelet spreading on spike protein and the increased phosphorylation of the β‐integrin tail, c‐Src, and Syk (Figure 4A–D), we explore whether 1,25(OH) 2 D 3 could inhibit outside‐in signaling induced by spike protein. Firstly, spike protein contains an arginine‐glycine‐aspartic acid (RGD)‐containing motif that enables it to bind with platelet integrin β3, 3 indicating resting platelets can adhere to immobilized spike protein similarly to how they adhere to immobilized fibrinogen, thereby resulting in platelet spreading 18 . So we conducted a platelet spreading assay on immobilized spike protein and observed that 10 nM 1,25(OH)2D3 significantly reduced the surface area of spread platelets on the immobilized spike protein (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we found that spike protein could upregulate platelet integrin αⅡbβ3 outside‐in signaling, such as platelet spreading on spike protein and the increased phosphorylation of the β‐integrin tail, c‐Src, and Syk (Figure 4A–D), we explore whether 1,25(OH) 2 D 3 could inhibit outside‐in signaling induced by spike protein. Firstly, spike protein contains an arginine‐glycine‐aspartic acid (RGD)‐containing motif that enables it to bind with platelet integrin β3, 3 indicating resting platelets can adhere to immobilized spike protein similarly to how they adhere to immobilized fibrinogen, thereby resulting in platelet spreading 18 . So we conducted a platelet spreading assay on immobilized spike protein and observed that 10 nM 1,25(OH)2D3 significantly reduced the surface area of spread platelets on the immobilized spike protein (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous study has found that SARS‐CoV‐2 spike protein interacted with integrin αIIbβ3, 3 which could upregulate the outside‐in signaling pathway to potentiate platelet aggregation. Platelet integrin αIIbβ3 outside‐in signaling induces stabilized platelet aggregation and also plays a crucial role in the process of thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Platelets are key in innate immunity, and their overactivation in sepsis can promote microthrombosis and exacerbate inflammatory response, resulting in thrombocytopenia, DIC, and multiple organ dysfunction, ultimately leading to death [ 3 , 36 38 ]. Evidence shows that antiplatelet drugs like clopidogrel can mitigate sepsis-induced inflammation and organ dysfunction [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last several months, a wave of studies has focused on the experimental modeling of platelet activation by variants of the Spike protein. The first study showed that the spike protein can bind integrins αIIbβ3 (glycoprotein IIb-IIIa) and activate platelets, with Kappa and Delta having stronger effects relative to the wild type [123]. Proteinprotein interaction studies revealed that platelet integrins bind to the RGD sequences in the Spike protein of Alpha but not wild type or Omicron [124].…”
Section: Evolution Of Coronavirus and Its Hematological Interactionsmentioning
confidence: 99%
“…The canonic ACE2 entry has not yet been either proven or ruled out, and most likely there are alternative entry routes in any case [19,25,40,41,44,48,124]. It is interesting to note that the early cell-based studies on SARS-CoV-2 entry mechanisms [40][41][42]45,48] and recent studies on platelet interactions with recombinant Spike proteins focusing on platelet activation [123][124][125][126][127] appear to represent two different strategic approaches with different results. Their combination might shed light on both issues of entry and platelet activation by the virus.…”
Section: Problems and Their Statusmentioning
confidence: 99%